Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's analyze each pair of functions step by step to determine the compositions [tex]\( f(g(x)) \)[/tex] and [tex]\( g(f(x)) \)[/tex], and then check whether [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are inverses.
## Pair (a)
Given functions:
[tex]\[ f(x) = x + 3 \][/tex]
[tex]\[ g(x) = x - 3 \][/tex]
### Step 1: Calculate [tex]\( f(g(x)) \)[/tex]
[tex]\[ g(x) = x - 3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(x - 3) = (x - 3) + 3 = x \][/tex]
### Step 2: Calculate [tex]\( g(f(x)) \)[/tex]
[tex]\[ f(x) = x + 3 \][/tex]
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(x)) = g(x + 3) = (x + 3) - 3 = x \][/tex]
Since both compositions [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex], [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are indeed inverses of each other.
## Pair (b)
Given functions:
[tex]\[ f(x) = -\frac{1}{4x}, x \neq 0 \][/tex]
[tex]\[ g(x) = \frac{1}{4x}, x \neq 0 \][/tex]
### Step 1: Calculate [tex]\( f(g(x)) \)[/tex]
[tex]\[ g(x) = \frac{1}{4x} \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{4x}\right) = -\frac{1}{4 \left(\frac{1}{4x}\right)} = -\frac{1}{\frac{1}{x}} = -x \][/tex]
### Step 2: Calculate [tex]\( g(f(x)) \)[/tex]
[tex]\[ f(x) = -\frac{1}{4x} \][/tex]
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(-\frac{1}{4x}\right) = \frac{1}{4 \left( -\frac{1}{4x} \right)} = \frac{1}{-\frac{1}{x}} = -x \][/tex]
Since neither composition [tex]\( f(g(x)) = -x \)[/tex] nor [tex]\( g(f(x)) = -x \)[/tex] simplifies to [tex]\( x \)[/tex], [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are not inverses of each other.
## Summary:
(a) For [tex]\( f(x) = x + 3 \)[/tex] and [tex]\( g(x) = x - 3 \)[/tex]:
[tex]\[ f(g(x)) = x \][/tex]
[tex]\[ g(f(x)) = x \][/tex]
[tex]\( f \)[/tex] and [tex]\( g \)[/tex] are inverses of each other.
(b) For [tex]\( f(x) = -\frac{1}{4x}, x \neq 0 \)[/tex] and [tex]\( g(x) = \frac{1}{4x}, x \neq 0 \)[/tex]:
[tex]\[ f(g(x)) = -x \][/tex]
[tex]\[ g(f(x)) = -x \][/tex]
[tex]\( f \)[/tex] and [tex]\( g \)[/tex] are not inverses of each other.
## Pair (a)
Given functions:
[tex]\[ f(x) = x + 3 \][/tex]
[tex]\[ g(x) = x - 3 \][/tex]
### Step 1: Calculate [tex]\( f(g(x)) \)[/tex]
[tex]\[ g(x) = x - 3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(x - 3) = (x - 3) + 3 = x \][/tex]
### Step 2: Calculate [tex]\( g(f(x)) \)[/tex]
[tex]\[ f(x) = x + 3 \][/tex]
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(x)) = g(x + 3) = (x + 3) - 3 = x \][/tex]
Since both compositions [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex], [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are indeed inverses of each other.
## Pair (b)
Given functions:
[tex]\[ f(x) = -\frac{1}{4x}, x \neq 0 \][/tex]
[tex]\[ g(x) = \frac{1}{4x}, x \neq 0 \][/tex]
### Step 1: Calculate [tex]\( f(g(x)) \)[/tex]
[tex]\[ g(x) = \frac{1}{4x} \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{4x}\right) = -\frac{1}{4 \left(\frac{1}{4x}\right)} = -\frac{1}{\frac{1}{x}} = -x \][/tex]
### Step 2: Calculate [tex]\( g(f(x)) \)[/tex]
[tex]\[ f(x) = -\frac{1}{4x} \][/tex]
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(x)) = g\left(-\frac{1}{4x}\right) = \frac{1}{4 \left( -\frac{1}{4x} \right)} = \frac{1}{-\frac{1}{x}} = -x \][/tex]
Since neither composition [tex]\( f(g(x)) = -x \)[/tex] nor [tex]\( g(f(x)) = -x \)[/tex] simplifies to [tex]\( x \)[/tex], [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are not inverses of each other.
## Summary:
(a) For [tex]\( f(x) = x + 3 \)[/tex] and [tex]\( g(x) = x - 3 \)[/tex]:
[tex]\[ f(g(x)) = x \][/tex]
[tex]\[ g(f(x)) = x \][/tex]
[tex]\( f \)[/tex] and [tex]\( g \)[/tex] are inverses of each other.
(b) For [tex]\( f(x) = -\frac{1}{4x}, x \neq 0 \)[/tex] and [tex]\( g(x) = \frac{1}{4x}, x \neq 0 \)[/tex]:
[tex]\[ f(g(x)) = -x \][/tex]
[tex]\[ g(f(x)) = -x \][/tex]
[tex]\( f \)[/tex] and [tex]\( g \)[/tex] are not inverses of each other.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.